Conformational Study of Intermediate States of Papain in the Presence of Different Polarities of Alcohols - HESHMATI, M.; CHAMANI, J.; RAJABI, O.; PARIVAR, K. (Asian Journal of Chemistry, 2010)
Our studies extend on the presence of intermediate state of papain at two different pH values in the presence of different kind of alcohols. A systematic investigation of the effect of aqueous alcohols on the structure of partially unfolded state at pH 3.2 and the native-like state at pH 5.0 was made using intrinsic tryptophan fluorescence and UV-visible spectroscopy. Tryptophan fluorescence studies indicate that the change in the environment of the tryptophan residue on the addition of alcohols would result in a decrease in the fluorescence intensity at pH 3.2 and 5.0. These decreases in the fluorescence intensity of papain at pH 3.2 and 5.0 can be attributed to the conformational changes in the surfaceexposed tryptophan, presumably due to internal changes in a more hydrophobic environment and formation of a more compact structure. This suggest that alcohols which steer the conformational changes in the direction of the formation of native-like state and unfolded state at the two pH values of 3.2 and 5.0, respectively, lead to the formation of intermediate states along the two aforementioned pathways. UV measurement studies that indicate at pH 5.0, the addition of alcohol leads to an increase in the absorbance and demonstrate the formation of IB and IC states on the transition of the native-like state to the unfolded state. The native and partially unfolded states have different intermediates. In the present work, comparison of the results of fluorescence experiments shows more positive m-values as a cooperative parameter for intermediate state at pH 3.2. These effects of alcohols can be explained to some extent, by the decreased polarity of the solvent. In solvents of low polarity, hydrophobic interactions stabilizing native structures or protein aggregates are weakened and simultaneously the local hydrogen bonds are strengthened, resulting in denaturation or dissolution and stabilization of the extended a-helical structures.